ХАЛЫҚ ҚОСЫҚЛАРЫНЫҢ ПАЙДА БОЛЫЎЫНДА ИНДИВИДУАЛ ДӨРЕТИЎШИЛИКТИҢ ТУТҚАН ОРНЫ - Бауатдинова, С. (ILIM hám JÁMIYET, 2020)
The article discusses the role of folk poets in the emergence of folk songs. "Poets of the people" are creative people who are able to improvise, express their natural talent, use modern poetry of folk poetry. The article also provides examples of how folk poets create their works in an oral and memorable way, thereby quickly distributing their songs.